Técnicas de integração de circuitos de auxílio à comutação aplicadas a inversores e a sistemas multi-pólos - Russi, Jumar Luís (2007)
This Ph. D. dissertation presents contributions to the investigation of soft-switching cells with integrated components, presenting three main approaches: (i) Soft-switching cells with filter coupled inductor; (ii) Integrated soft-switching cells of the ZVT type for multipole systems; and (iii) Integrated soft-switching cells for several soft-switching techniques for multipole systems. Firstly it is presented a generic diagram for softswitching inverters with coupled filter inductor. From the generic diagram the turn-on snubber, ZVT and ZCZVT inverters topologies are derived. It is based on an auxiliary loop, which presents an inductor coupled to the filter inductor. The magnetic coupling allows annulling the current through the main switches during the switching transitions and, as a result, reducing the commutation losses. The basic differences among the techniques obtained by this method are the way of implementing the auxiliary switches and the time instants when these switches are triggered. The topological variations are a result of the choice of the voltage applied through the auxiliary loop by its connection to the inverter topology. Analytical expressions for the derived topologies are obtained aiming to evaluate the operation conditions, as well the main features of each topology. It is proposed a design procedure for each derived topology and the operation principles of each topology are verified by means of experimental and simulation results. Then the integrated softswitching cells of the ZVT type for multipole systems are studied. The synthesis methodology presented is based on generating every topological possibility of symmetrical auxiliary cells. The redundant cells are removed from the set of generated topologies resulting in only four diagrams, which are used to derive the integrated ZVT converters already known in the literature, as well several yet unpublished. The synthesis methodology is applied on an interruptible power supply system, which is experimentally evaluated. Finally it is proposed a generalized methodology to obtain integrated auxiliary commutation cells from several soft-switching techniques concerning multipole systems. The integration possibilities among the models obtained for the chosen soft-switching techniques are investigated, resulting in integrated models. The practical implementation of the resulting models is studied originating integrated topologies for multipole systems. The poles of the system can present the same soft-switching technique or different ones. Experimental results are presented in order to validate the concepts proposed herein.